Characteristics of the crime of theft and its perpetrator based on court proceedings (Archives of Criminology, 2023)
This article compares the features of contemporary theft and its perpetrators with the characteristics of theft before the transformation in Poland. For this purpose, two studies on theft were compared – one from 2017 and one from 1979. This procedure made it possible to compare the objects of theft, the way it is perpetrated, the characteristics of its perpetrators, and the methods by which it is detected, as well as the punitive measures applied. The material gathered showed both differences and consistencies in the compared cases.